Recruitment of specific flavonoid B‐ring hydroxylases for two independent biosynthesis pathways of flavone‐derived metabolites in grasses. Issue 1 (13th April 2019) - Lam, Pui Ying; Lui, Andy C.W.; Yamamura, Masaomi; Wang, Lanxiang; Takeda, Yuri; Suzuki, Shiro; Liu, Hongjia; Zhu, Fu‐Yuan; Chen, Mo‐Xian; Zhang, Jianhua; Umezawa, Toshiaki; Tobimatsu, Yuki; et al.
Summary: In rice ( Oryza sativa ), OsF2H and OsFNSII direct flavanones to independent pathways that form soluble flavone C ‐glycosides and tricin‐type metabolites (both soluble and lignin‐bound), respectively. Production of soluble tricin metabolites requires CYP75B4 as a chrysoeriol 5′‐hydroxylase. Meanwhile, the close homologue CYP75B3 is a canonical flavonoid 3′‐hydroxylase (F3′H). However, their precise roles in the biosynthesis of soluble flavone C ‐glycosides and tricin–lignins in cell walls remain unknown. We examined  CYP75B3 and CYP75B4 expression in vegetative tissues, analyzed extractable flavonoid profiles, cell wall structure and digestibility of their mutants, and investigated catalytic activities of CYP75B4 orthologues in grasses. CYP75B3 and CYP75B4 showed co‐expression patterns with OsF2H and OsFNSII, respectively. CYP75B3 is the sole F3′H in flavone C ‐glycosides biosynthesis, whereas CYP75B4 alone provides sufficient 3′, 5′‐hydroxylation for tricin–lignin deposition. CYP75B4 mutation results in production of apigenin‐incorporated lignin and enhancement of cell wall digestibility. Moreover, tricin pathway‐specific 3′, 5′‐hydroxylation activities are conserved in sorghum CYP75B97 and switchgrass CYP75B11. CYP75B3 and CYP75B4 represent two different pathway‐specific enzymes recruited together with OsF2H and OsFNSII, respectively. Interestingly, the OsF2H‐CYP75B3 and OsFNSII‐CYP75B4 pairs appear to be conserved in grasses. Finally, manipulation of tricin biosynthesis through CYP75B4 orthologues can be a promising strategy to improve digestibility of grass biomass for biofuel and biomaterial production.